La gimnasia acuática y el trastorno de la marcha - Arcos Buñay, Carlos Daniel (2023)
This case study investigated the influence of a 12-week aquatic gymnastics exercise program on the physical development of children with gait disorders. Individualized aquatic gymnastics sessions were designed and implemented, focusing on improving specific aspects of gait and strengthening the muscles involved in movement. Variables such as muscle strength, cardiovascular endurance, motor coordination, and gait quality were assessed before and after the intervention. The results showed significant improvements in all measured variables after completing the aquatic gymnastics program. Both participants experienced increased muscle strength, improvements in cardiovascular endurance, and enhanced motor coordination. Furthermore, an improvement in gait quality was observed, reflected in greater stability and fluidity of movement. Qualitative data collected through direct observations and interviews with the participants and their families supported the quantitative findings, indicating a positive perception of the benefits of aquatic gymnastics. Participants and their families reported increased confidence in motor skills, greater autonomy in performing daily activities, and an overall improvement in quality of life. These findings support the effectiveness of aquatic gymnastics as a therapeutic intervention for children with gait disorders and highlight the importance of individualized, evidence-based exercise programs. These results may have significant implications in clinical practice by providing an effective and non-invasive therapeutic option for enhancing motor functionality and quality of life in children with gait disorders.